Application of Resistivity Geoelectric to Determine the Seawater Intrusion Zone in the Sungai Kakap District - Ahmad Mushawwir; Yoga Satria Putra; Radhitya Perdhana (PRISMA FISIKA, 2022)
The application of the resistivity geoelectric method has been carried out in a study to determine the seawater intrusion zone in Sungai Kakap District, Kuburaya Regency using the Wenner-Schlumberger configuration. This research used Automatic Resistivity System Multielectrode (ARES). The research was carried out by arranging the 5 tracks.  The first, second, fourth and fifth tracks have a track length of 117 m. While the third track has a track length of 93 m. The distance between the electrodes is 3 m. The results showed that seawater intrusion that occurred in each track had resistivity value range between 0.2 Ωm to 2.77 Ωm. Seawater intrusion found in layers with sand material. Keyword : sea water intrusion, geoelectrical, resistivity, Wenner-Schlumberger